2014
DOI: 10.1260/1747-9541.9.2.367
|View full text |Cite
|
Sign up to set email alerts
|

Coaches, Athletes, Skill Acquisition Specialists: A Case of Misrecognition

Abstract: Skill acquisition specialists are sport scientists who examine the theories, principles and processes of motor and perceptual learning. The research generated by these specialists is applied to practice modes, feedback and instructional methods, decision-making and anticipation skills training for athletes. However, unlike most sports scientists, these specialists are not utilized to the same degree as their counterparts. Therefore, the purpose of this study was to investigate why this trend exists. Forty two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 14 publications
1
25
0
Order By: Relevance
“…The interdisciplinary (multivariate analysis) approach in our study revealed that psychological and perceptual-cognitive-motor components of individual constraints contributed to significantly predict disposal efficiency. This finding is consistent with coach perception that superior performance in sport is related to psychological and perceptual-cognitive-motor skills (Steel et al, 2014 ; Zaichkowsky and Peterson, 2018 ). A likely reason for this is that coping with psychological pressure and making accurate decisions allows the player to apply their physical capability efficiently (less energy cost) to dispose of the ball effectively.…”
Section: Discussionsupporting
confidence: 85%
“…The interdisciplinary (multivariate analysis) approach in our study revealed that psychological and perceptual-cognitive-motor components of individual constraints contributed to significantly predict disposal efficiency. This finding is consistent with coach perception that superior performance in sport is related to psychological and perceptual-cognitive-motor skills (Steel et al, 2014 ; Zaichkowsky and Peterson, 2018 ). A likely reason for this is that coping with psychological pressure and making accurate decisions allows the player to apply their physical capability efficiently (less energy cost) to dispose of the ball effectively.…”
Section: Discussionsupporting
confidence: 85%
“…This variety of understanding of how a sport science discipline can support a coach has previously been reported as occurring with skill acquisition specialists. 1,19 The role of the biomechanist in altering coaches' understanding of biomechanics was explored as part of the coach education theme that was prominent in the interviews.…”
Section: Resultsmentioning
confidence: 99%
“…Given the coaches' goal of integrating 'scientifically-driven literature' into practice within the fast-paced coaching environment (Williams & Kendall, 2007), it has been suggested that coaches place value in working with a "mediator" who can translate and transfer knowledge from scientific sources into mediums that are more accessible (Williams & Kendall, 2007;Steel, Harris, Baxter, King, & Ellam, 2014). Considering the support services available to coaches, particularly at the elite level, one potential solution to this issue is working in conjunction with a skill acquisition (SA) specialist who could act as an ally and resource (Lyle, 2018).…”
Section: The Skill Acquisition Specialist As a Mediatormentioning
confidence: 99%
“…A SA specialist has been identified as a sport scientist that 'examine[s] the theories, principles and processes of motor and perceptual learning' (Steel et al, 2014, Pg. 1) and works closely with coaches and athletes to bridge the gap between theory and practical application (Steel et al 2014;Williams & Ford, 2009;Williams, Ford, Causer, Logan, & Murray, 2012).…”
Section: The Skill Acquisition Specialist As a Mediatormentioning
confidence: 99%
See 1 more Smart Citation